P Peningkatan Pengetahuan Wanita Tentang Pencegahan Kanker Serviks (Prosiding Seminar Nasional Masyarakat Tangguh, 2024)
Cervical cancer is a type of disease that endangers a woman's life. However, cervical cancer can be detected earlier in order to get earlier treatment. Early detection is carried out by the IVA method or pap smears carried out in women who have had sexual intercourse with an age range of 30 to 50 years. This test aims to find lesions and detect cell changes in the cervix. Women's ability to carry out early detection is in line with women's knowledge about cervical cancer prevention. Therefore, behavior change can occur starting with an increase in knowledge. The method used in this activity is material presentation, discussion and question and answer, feedback which is carried out online with the target being women. The result of this activity is that women can find out how to prevent cervical cancer. A healthy society begins with an independent community that is aware of its health needs.